Intake, Nutrient Digestibility, and Growth Performance of Balinese Bulls Fattening on Various Types of Forages in Traditional Farm - Paulus Klau Tahuk; Agustinus Agung Dethan; Stefanus Sio (ANIMAL PRODUCTION, 2023)
This study aimed to evaluate the performance of Balinese bulls fattened by various forages on traditional farms. The study was experimental research using Clitoria ternatea, Zea mays fresh straw, Pennisetum purpuphoides, Pennisetum purpureum, Sesbania grandiflora, Centrosema pubescens, Leucaena leucocephala, and natural grass to fatten the livestock which were arranged for the farmers' habits in fattening. Variables measured included feed consumption and digestibility and livestock growth performance, including daily body weight gain (PBBH), feed conversion and efficiency, and feed cost per gain. The collected data were then analysed using descriptive analysis procedures. The results showed that fattening Balinese bulls with forage resulted in dry matter (DM) (kg/head/day) reaching 7.079, while crude protein (CP) and organic matter (OM) intake were respectively 1.053 and 6.440 (kg/head/day). The digestibility coefficient of dry matter was 56.68%, crude protein was 69.86%, and organic matter was 68.83%. The ADG obtained by livestock was 0.321 kg/head/day; meanwhile, the feed conversion and efficiency were respectively 23.664 kg.DM/kg.ADG and 4.619%; the feed cost per gain (IDR/kg.ADG) reached 10,813.85. To sum up, the use of various types of forage in fattening Balinese bulls on traditional farms indicates that DM, OM, and CP intake are relatively high, but it provides relatively low feed digestibility by mean of ADG, conversion, and feed efficiency are not optimal.